MENULIS SEBAGAI WACANA PENGEMBANGAN PERSONAL DIRI DAN BRANDING BERBASIS DIGITAL DI YAYASAN PENDIDIKAN SHAFIYATUL AMMALIYAH MEDAN - Aisyah, Nur; Meutia, Riza Fanny (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This Community Service activity is carried out at the Shafiyatul Ammaliyah Education Foundation which manages schools that have preschools, elementary schools, middle schools and high schools in the Jl. Setia Budi 119 Medan City, North Sumatra Province. There are approximately 100 teachers from undergraduate and graduate degrees who manage the teaching and learning process. Based on the results of discussions and meetings with the Principal of Shafiyatul Ammaliyah High School, several facts and problems faced by teachers at Shafiyatul Ammaliyah were obtained. That along with the development of IT and digitalization and increasingly scientific knowledge, it is hoped that the participation of Shafiyatul Ammaliyah High School teachers will be able to develop their potential in terms of pouring the knowledge taught into written form in the form of books and can increase the body of knowledge which will help the Education Foundation Shafiyatul Ammaliyah. With the development of digitalization technology, it is necessary to provide training to these teachers while exploring their own potential and keeping up with IT which continues to develop in carrying out teaching and learning processes in the form of improving human resource management and understanding the need for writing, in increasing the knowledge of Shafiyatul Ammaliyah High School teachers, Jl. Setia Budi Medan, North Sumatra.